Metabolically healthy obese patients - Pajuelo R., Jaime (2014)
Introduction: Obesity is a public health problem that tends to increase and compromises the health of people. Objectives: To determine the prevalence of metabolically normal obese (OMN) subjects depending on the presence of cardiovascular risk factors in an adult population showing obesity and morbid obesity. Design: Observational, descriptive and cross-section study. Setting: Department of Endocrinology, Hospital Dos de Mayo, Lima, Peru. Participants: Obese adults without metabolic diseases. Interventions: the study was conducted during the period between April 2009 and May 2010 in all adults consulting for obesity and who declared not having type 2 diabetes mellitus, arterial hypertension or dyslipidemia. Weight, height and waist circumference (WC) were obtained, and body mass index (BMI) was calculated. Those who had 30 kg/m2 or more were included in the study. Insulin, glucose and lipid profile were determined. Metabolic syndrome was determined through measurement of glucose, HDL-C, triglycerides and WC. Insulin resistance (IR) was diagnosed through glucose and insulin resistance homeostasis model assessment (HOMA-IR). Two groups were distinguished: obese with BMI of 30 to 39.9 kg/m2, and obese with BMI 40 kg/m2 and more. Statistical analysis was performed using student t test and chi -square with a 95% confidence interval and a significance level of < 0.05. Main outcome measures: Average and standard deviation variables. Prevalence of OMN and OMnotN. Results: From the 158 subjects, 91.2 % were female The OMN and OMnotN groups showed statistically significant difference in weight, height, WC, insulin and HOMA-IR. OMN prevalence was 7% in all obese and 7.3 and 6.4% in the BMI groups (Wildman criteria), while it was 13%, 15.5 and 2.1 % respectively by Meiggs criteria. Conclusions: The study showed the presence of a reduced number of obese subjects considered OMN by the criteria used.